Dis/ability-sensible Kirchengeschichte - Dierk, Heidrun (Evangelische Theologie, 2026)
This article aims to show the extent to which the questions and perspectives of Dis/ability history can provide impetus for Church history and Christian history for gaining new insights. To this end, the author first explains her understanding of Church and Christian history and where there are points of contact with Dis/ability studies and Dis/ability history. Using the phenomenon of leprosy as an example, it will be shown to what extent medical, socio-historical, and religious-cultural perspectives are involved in dealing with leprosy patients and how they influence and permeate each other.